Cancer treatment-induced thrombocytopenia: diagnosis, mechanisms and management - Zhao, Xutong; Shan, Xiu; Sui, Shaofeng; Song, Qinghao; Cheng, Miao; Zhao, Yi (Frontiers in Immunology, 2025)
Cancer treatment-induced thrombocytopenia (CTIT) is a common adverse effect in malignant tumor patients, significantly increasing the risk of bleeding and negatively impacting treatment efficacy and quality of life. Current treatment options for CTIT primarily include platelet transfusion, recombinant human interleukin-11 (rhIL-11), recombinant human thrombopoietin (rhTPO) and thrombopoietin receptor agonists (TPO-RAs). However, these methods have their limitations; for instance, platelet transfusions may cause adverse reactions, and the efficacy and safety of rhTPO and TPO-RAs remain controversial. This review aims to summarize the current treatment landscape for CTIT and explore new therapeutic advancement, including the potential role of traditional Chinese medicine, in order to provide more effective treatment strategies for clinical practice.